If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6m + 13 = 4m + 3 Reorder the terms: 13 + 6m = 4m + 3 Reorder the terms: 13 + 6m = 3 + 4m Solving 13 + 6m = 3 + 4m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-4m' to each side of the equation. 13 + 6m + -4m = 3 + 4m + -4m Combine like terms: 6m + -4m = 2m 13 + 2m = 3 + 4m + -4m Combine like terms: 4m + -4m = 0 13 + 2m = 3 + 0 13 + 2m = 3 Add '-13' to each side of the equation. 13 + -13 + 2m = 3 + -13 Combine like terms: 13 + -13 = 0 0 + 2m = 3 + -13 2m = 3 + -13 Combine like terms: 3 + -13 = -10 2m = -10 Divide each side by '2'. m = -5 Simplifying m = -5
| 2k+k+45= | | X-7/4=2 | | X(3X+9)=264 | | -6(x+6)-5=2(x+7) | | 12w-8w-3w=12 | | 4g=144 | | -14w+7-20+12w= | | -42-7y=-105 | | -8y+11=83 | | U-6=-8 | | F/81=-3 | | m^3-6m^2+9m-3=0 | | -5y-4(4y-1)=3-1(3-y) | | 6x-5x=-105+98 | | z-8/15=2/15 | | .3x+1.5=-3.5x-3 | | (2-7x)=(-4x+8) | | 16y=-11x+13 | | x^2-2x-2kx+2k=0 | | 2(x-4)-(8x+10)=x-14 | | 2x-3=-2x-6 | | 4x-6=14x-8 | | 5-4(5x-3)+8=134 | | 3x-4y+5z=9 | | https://www.vle.mathswatch.com/images/questions/question3802.pn | | 3x-33=21 | | 130=-18-(7y-8) | | 7x-56=5x+10 | | -4x+15=16x+20 | | 4x^2+4x+4=x+3 | | 6x^2-38x=-32 | | 9+u=-3 |